IMPLEMENTATION OF THE PROSECUTOR'S AUTHORITY IN THE IMPLEMENTATION OF JUSTICE FOR VICTIMS OF NARCOTICS ABUSE ACCORDING TO POSITIVE LAW - Andri Ridwan; Adang Djumhur Salikin; Sugianto Sugianto; Didi Sukardi; Andi Lala (Faculty of Law, Universitas Pekalongan, 2025)
Narcotics pose a global issue that jeopardizes public order and endangersboth physical and mental well-being. Narcotics usage in Indonesia hasevolved into a multifaceted issue with extensive ramifications,encompassing legal, social, psychological, and humanitarian dimensions.This study aims to evaluate the prosecutor's authority in implementingrestorative justice for victims of narcotics misuse, in accordance withstatutory legislation. The employed methodology is a qualitativedescriptive approach. Data was acquired through comprehensive surveysand conversations with prosecutors regarding the execution of theirpowers. What is the function of the prosecutor's office within the criminaljustice system concerning positive law? Describing Narcotics AbuseCases through Restorative Justice by the Prosecutor's Office TheRestorative Justice Approach serves as an application of the Prosecutor'sDominus Litis Principle, allowing the Prosecutor's Office the discretionto cease prosecution of narcotics abuse suspects, thereby fostering ajustice system that prioritizes rehabilitation over mere criminalization.